THE SCEPTRE (KEKUASAAN) DAN THE SPECTRE (HANTU): DUA WAJAH POPULISME DALAM DEMOKRASI (LIBERAL) - Sabarudin, Didin; Ghassani, Rizqi (LEMBAGA PUSAT KAJIAN KEBANGSAAN/PUSKAB UKRI, 2025)
The phenomenon of populism emerged in contemporary politics in the era of global democracy, including Indonesia, with the trigger being the economic and political crisis. Populism has a positive meaning in (liberal) democracy by placing antagonistic discourse to fight for the values ​​of justice, equality, prosperity, and fairness for the populus which reveals the corruption of the other, the political and business elite in the sceptre (power) of the oligarchy. Populist actors move dynamically and flexibly in the name of the populus as the spectre of the oligarchy by carrying out propaganda of resistance against the sceptre which is corrupt, oligarchic, and oppressive to the people. They fight for the improvement of the people's fate and play an antagonistic role against the oligarchic elite, corruption, globalization with its neo-liberalism. However, populism has a negative meaning as an effort to find a vehicle and entry ticket as a new player in the oligarchy, so that populism becomes rhetoric for efforts to seize power because it was born as part of the oligarchy vortex. That is the purpose of this writing with a critical study as a political philosophy approach using a qualitative explanatory method to examine the changes in the term populism since its emergence as a form of opposition to oligarchic power in (liberal) democracy whose boundaries are no longer clear. Populism can be a transformative force in Indonesia with an antagonistic role against the increasingly strong oligarchic power. However, it failed as an antagonistic anti-status quo and emancipatory force because it also perpetuated the sceptre of corrupt and greedy oligarchy, even forming a final identity as a shadow democratic power, instead of becoming the spectre of oligarchic power.